Metabolic disturbances in male broilers of different strains. 2. Relationship between the thyroid and somatotropic axes with growth rate and mortality - Gonzales, Elisabeth [UNESP]; Buyse, Johan; Sartori, José Roberto [UNESP]; Loddi, Maria Marta [UNESP]; Decuypere, Eddy (Elsevier, 1999)
Seven male broiler strains (Arbor Acres, Avian Farms, Cobb-500, Hubbard-Peterson, ISA, Naked Neck, and Ross) were compared for their growth rate, feed efficiency, and mortality due to sudden death and ascites. In addition, weekly plasma levels of thyroid hormones [3,3′,5-triiodothyronine (T3) thyroxine (T4), T3: T4 ratio, growth hormone (GH), and insulin-like growth factor-I (IGF-I)] were determined. The highly productive, commercial strains were very similar in their endocrine profiles but differed markedly from the Naked Neck chickens. Naked Neck chickens were characterized by higher plasma T3 and lower T4 levels at similar ages as well as when compared on the same body weight basis. The present findings support the hypothesis that the slightly hypothyroid state of high productive broilers renders them more sensitive to metabolic disorders. Naked Neck chickens also had higher plasma GH levels than those of their age-matched commercial broilers. The coefficient of variation for GH was highest for Naked Neck chickens, which is indicative for an amplified GH burst amplitude. It may be stated that changes in plasma thyroid hormone concentration in indirect response to selection for low feed conversion and fast growth may be causatively linked to susceptibility for metabolic disturbances such as sudden death syndrome and ascites.
Keywords: Broiler strains; Naked Neck; Performance; Somatotropic axis; Thyroid hormones; growth hormone; liothyronine; somatomedin C; thyroxine; aging; animal; animal disease; bird disease; blood; chicken; comparative study; death; growth, development and aging; male; metabolic disorder; metabolism; pathophysiology; physiology; species difference; thyroid gland; Aging; Animals; Chickens; Death; Growth Hormone; Insulin-Like Growth Factor I; Male; Metabolic Diseases; Poultry Diseases; Species Specificity; Thyroid Gland; Thyroxine; Triiodothyronine